Effectiveness of Communication Strategies for Tobacco Intervention: A Systemic Review and Finding the Right Approach - Bhargava, Shruti (Digital Repository of Theses, 2025)
Communication is one of the most important tool that aid to connect to the people. The Concept which is used in this research is a mixed method, combines qualitative and quantitative approaches to provide a more holistic understanding of research questions, the result of this research shows the positive approach towards the development of the effective communication strategy for the Tobacco intervention. The tool used in this research is google form in view of Simple Seven Questionnaire. According to the World Health Organization (WHO) Tobacco is the single greatest cause of preventable death across globe. Awareness is required regarding the ill effects of Tobacco use so that with the correct knowledge and attitude, gradual but marked difference can be made and appreciated.